The literary representation of identity and alienation in counterinsurgencies - Senekal, Burgert A. (University of the Free State, 2013)
This interdisciplinary study investigates how alienation manifests in American literature on the Vietnam War and Afrikaans literature on the war in Namibia/Angola (the so-called Border War). After an historical contextualisation, the sociological branch of alienation theory, which is based on the writings of Melvin Seeman, is discussed, and it is illustrated how the six aspects of alienation, as identified by Seeman, manifest in several texts on these wars. In keeping with the interdisciplinary nature of the thesis, insights from alienation theory are integrated with theories of historiography, trauma, masculinity, and counterinsurgencies, all in an attempt to come to a better understanding of the texts under consideration. Despite literary theory’s insistence that alienation is a feature of modernist and postmodernist literature, and literature on these counterinsurgencies in particular, little has been written on what alienation actually is. Seeman’s variant was chosen because it is the most detailed and comprehensive treatment of alienation available, and although published in 1959, Seeman’s notion of alienation continues to be relevant within sociology. Seeman’s six aspects of alienation include powerlessness, meaninglessness, normlessness, cultural estrangement, social isolation, and self-estrangement, and these are used to discuss the literature on these two counterinsurgencies, highlighting how these aspects of alienation manifest in a variety of literary texts. The line between history and fiction is of course also an important boundary challenged by literature on these wars, and therefore a section is included under meaninglessness that deals with the writing of history and the role historical fiction plays in representing the past. Under cultural estrangement, a section is also included on masculinity, because since the army was often seen as offering a rite of passage, alienation manifests in this sense as well by rejecting the cultural values of masculinity. A section is also included on the alienating effects of trauma, because trauma is of course an important facet of literature on these wars, and it is shown how alienation ties in with trauma through two texts in particular: Larry Heinemann’s Paco’s Story and Anthony Feinstein’s Kopwond (released in English as Battle Scarred). Lastly, the study discusses all six aspects of alienation in reference to two of the seminal texts on these wars: Tim O’Brien’s If I die in a combat zone and Alexander Strachan’s ‘n Wêreld sonder grense. In general, the thesis tries to come to terms with the complexities of these wars: history, alienation, and identity are complex issues in these conflicts, and the interpretation of literary texts can be done from an extensive variety of perspectives. It is shown how alienation theory provides a useful prism for looking at these texts that stem from two watershed conflicts that changed their societies irrevocably.

Hierdie interdissiplinere studie ondersoek hoe vervreemding manifesteer in Amerikaanse literatuur oor die Vietnamoorlog en Afrikaanse literatuur oor die oorlog in Namibie/Angola (die sogenaamde Grensoorlog). Na 'n historiese kontekstualisering word die sosiologiese tak van vervreemdingsteorie, wat op die geskrifte van Melvin Seeman gebaseer is, bespreek, en daar word geillustreer hoe die ses aspekte van vervreemding, soos geidentifiseer deur Seeman, in 'n aantal van die tekste oor hierdie oorloe uitgebeeld word. In ooreenstemming met die interdissiplinere aard van die tesis, word insigte vanuit vervreemdingsteorie geintegreer met teoriee van geskiedskrywing, trauma, manlikheid, en teeninsurgensies, almal in 'n poging om tot 'n beter begrip van die tekste onder bespreking te kom. Ten spyte van literere teorie se aandrang daarop dat vervreemding 'n kenmerk van modernistiese en postmodernistiese literatuur is, asook literatuur oor hierdie teeninsurgensies in die besonder, is min geskryf oor wat vervreemding eintlik is. Seeman se variant is gekies omdat dit is die mees gedetailleerde en omvattende behandeling van vervreemding is wat beskikbaar is, en hoewel gepubliseer in 1959, is Seeman se opvatting van vervreemding steeds relevant in die sosiologie. Seeman se ses aspekte van vervreemding sluit in magteloosheid, betekenisloosheid, normloosheid, kulturele vervreemding, sosiale isolasie en selfvervreemding, en hierdie ses aspekte word gebruik om die literatuur oor hierdie twee teeninsurgensies te bespreek, met die klem op hoe hierdie aspekte van vervreemding in 'n verskeidenheid van literere tekste uitgebeeld word. Die lyn tussen geskiedenis en fiksie is natuurlik ook 'n belangrike grens wat uitgedaag word deur literatuur oor hierdie oorloe, en dus is ‘n afdeling ingesluit onder betekenisloosheid wat handel oor die skryf van die geskiedenis en die rol wat historiese fiksie speel in die uitbeelding van die verlede. Onder kulturele vervreemding is ook 'n afdeling ingesluit oor manlikheid, want sedert die weermag dikwels gesien is as 'n deurgangsrite, manifesteer vervreemding in hierdie sin ook deur die verwerping van die kulturele waardes van manlikheid. 'n Afdeling is ook ingesluit oor die vervreemdingseffekte van trauma, omdat trauma natuurlik 'n belangrike faset is van die literatuur oor hierdie oorloe, en dit word gewys hoe vervreemding skakel met trauma deur twee tekste in die besonder: Larry Heinemann se Paco’s Story en Anthony Feinstein se 'n Kopwond. Laastens bespreek die studie al ses aspekte van vervreemding met verwysing na twee van die seminale tekste oor hierdie oorloe: Tim O'Brien se If I die in a combat zone en Alexander Strachan se 'n Wêreld Sonder Grense. Oor die algemeen probeer die tesis om die kompleksiteit van hierdie oorloe aan te spreek: geskiedenis, vervreemding, en identiteit is komplekse kwessies in hierdie konflikte, en die interpretasie van literere tekste kan gedoen word uit 'n wye verskeidenheid van perspektiewe. Daar word gewys hoe vervreemdingsteorie 'n nuttige prisma bied om te kyk na hierdie tekste wat spruit uit twee waterskeidingskonflikte wat hul samelewings onherroeplik verander het.
Thesis (Ph.D. (Afrikaans and Dutch))--University of the Free State, 2013
Keywords: Alienation (Social psychology) in literature; Vietnam War, 1961-1975 -- Literature and the conflict; Counterinsurgency -- Nambia -- History -- 20th century; Counterinsurgency -- Angola -- History -- 20th century